Fiscal and monetary policy coordination and debt sustainability in the CEMAC zone: Evidence from a Markov regime-switching model - Makala, Ulrich Ekouala (Asian Journal of Economic Modelling, 2023)
This paper investigates the nature of fiscal and monetary policy implemented in the Economic and Monetary Community of Central Africa (CEMAC) and its impact on long-run debt sustainability. The study employs a two-state Markov regime-switching model to the fiscal and monetary policy reaction functions of the six CEMAC countries using time series data from 1970 to 2020. The fiscal regime is regarded as active if the coefficient of debt is positive, while it is considered passive if the coefficient is negative and significant. Regarding monetary policy, an active regime is reported if the coefficient of inflation is positive; otherwise, the monetary policy regime is regarded as passive. In addition, the transition probability and time-varying transition probability are estimated to assess the nature of policy-mix coordination. The findings highlight unsustainable fiscal regimes in Equatorial Guinea and Chad, balanced results for Gabon and Congo, while Cameroon and the Central African Republic have sustainable fiscal regimes. Concerning monetary policy, a sustainable monetary regime is found for Cameroon and Equatorial Guinea, with balanced results for Congo, while evidence of an unsustainable monetary regime is found for the Central African Republic, Chad, and Gabon.